Images and Illustrations to Build the Meaning in Arabic Dictionaries - El-Omari, Abdallah Hussein; Bataineh, Hussein Mohammad (Open Science Journal, 2018)
Current requirements to get dictionaries cope with the consequences of both the scientific and digital revolutions emphasize the importance of the methods to convey the accurate, exact and clear meaning which should not bear any error or the possibility of error to the recipient. Therefore, images and illustrations are among the means which are imposed on the science of lexicography making. That is why this research sheds light on this technique considering its nature, importance, peculiarities, functions, defects, and technicalities. The research also investigated the reality of images and illustrations in contemporary Arabic dictionaries and the difference between them and ancient ones.